Behavior of Francis turbines at part load. Field assessment in prototype: Effects on the hydraulic system. Issue 5 (March 2019) - Valero, Carme; Egusquiza, Mònica; Valentín, David; Presas, Alexandre; Egusquiza, Eduard
Abstract: At present, hydropower plants play an important role because of their flexibility in the generation of electricity. Today, the required operating range of turbine units is expected to extend to deep part load. At part load the draft tube vortex rope is generated and, in some cases, can produce large pressure pulsations limiting the operation of the turbine. The draft tube vortex rope has been much studied. In this paper, the effects of the part load behavior on the hydraulic system in existing power plants has been studied. Different hydropower units with Francis turbines has been selected for this purpose. All of them present strong vibrations in penstocks and other machine components at part load. Vibrations, pressure fluctuations and other parameters were measured in different positions of the turbine, the draft tube and the penstock. Signals were acquired during transients and for several operating loads. The signals in time and frequency domain and other signal treatments for these cases are shown.